Representasi Maskulinitas dalam Web-Series Peaky Blinders - Annisa Marta Siti Maharani Riskarna Putri (Jurnal Ilmu Komunikasi, 2021)
Web series are currently one of the best entertainment options for the public. Just like movies, web series also have the ability to imply messages to the audience. One of the best web series that has an implied message in it is Peaky Blinders. The purpose of this research is to find out the characteristic signs of masculine men in 3 characters namely Thomas Shelby, Arthur Shelby, and Alfie Solomons. This study uses a qualitative approach and semiotic analysis by Roland Barthes. Primary data is obtained directly from the Peaky Blinders web series which is watched via the Netflix platform, and secondary data is obtained from other scientific data sources. The results obtained are that in this film, men are depicted as having to think alone, being physically ready and looking muscular, and having to remain calm even when facing life-threatening situations.